DEVELOPMENT OF ENVIRONMENTAL EDUCATION IN THE WASTE MANAGEMENT SYSTEM - Zholdoshbekova Zh.; Kaldybaev B. K. (Vestnik Issyk-Kulʹskogo universiteta)
This article presents an analytical review of the solid waste management system in educational institutions. The existing positive experience in the development of the green movement and education of the younger generation in certain secondary schools and universities of Kyrgyzstan, for example, the Japanese Bilim Kan School, the American University of Central Asia, the I. Razakov Kyrgyz Technical University, the K. Tynystanov Issyk-Kul State University, where environmental projects in this direction are being implemented, is considered. Research in this area helps to develop strategies for environmental protection and sustainable development aimed at preserving natural resources and improving people's quality of life. Environmental initiatives and projects to restore ecosystems through waste recycling play a key role in creating a harmonious coexistence of man and nature. Educational organizations need to work more actively in this direction, to develop a culture of separate garbage collection and waste recycling among the younger generation.